Tapering of the thrombopoietin receptor agonist in paediatric patients with chronic immune thrombocytopenia: Is it possible?. Issue 9 (12th May 2022) - Solsona, María; Berrueco, Rubén; Sebastián, Elena; Cervera, Áurea; Sastre, Ana; Astigarraga, Itziar; Argilés, Bienvenida; Dasí, María Ángeles; Dapena, José Luís; Monteagudo, Emilio
Abstract : It is not clear if platelet responses are sustained after thrombopoietin receptor agonist (ar‐TPO) withdrawal in paediatric patients. A multicentre retrospective observational study was performed in children with chronic immune thrombopenia (cITP) to describe ar‐TPO tapering and withdrawal in patients who had achieved a sustained complete response to ar‐TPOs. Ten patients (eltrombopag n = 6, romiplostim n = 4) were included. Treatment withdrawal was performed after a mean tapering time of 7.6 months. Two patients relapsed (median follow‐up time of 24 months). Slow tapering and withdrawal of ar‐TPOs can be safely performed in cITP paediatric patients after achieving a sustained complete response.